2003
DOI: 10.1093/hmg/ddg143
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic benefits of cardiotrophin-1 gene transfer in a mouse model of spinal muscular atrophy

Abstract: Spinal muscular atrophy (SMA) is a recessive autosomal disorder characterized by degeneration of lower motor neurons caused by mutations of the survival motor neuron gene (SMN1). No curative treatment is known so far. Mutant mice carrying homozygous deletion of Smn exon 7 directed to neurons display skeletal muscle denervation, moderate loss of motor neuron cell bodies and severe axonal degeneration. These features, similar to those found in human SMA, strongly suggest the involvement of a dying back process o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
3

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(47 citation statements)
references
References 28 publications
1
43
0
3
Order By: Relevance
“…In spite of the severity of SMA phenotype in mutant mice, CT-1 is able to slow down disease progression. Neuroprotection could be regarded as valuable therapeutic approach in SMA 71 . CT-1 defi ciency causes increased motoneuron cell death in spinal cord and brainstem nuclei of mice during a period between embryonic day 14 and the fi rst postnatal week.…”
Section: Cancermentioning
confidence: 99%
“…In spite of the severity of SMA phenotype in mutant mice, CT-1 is able to slow down disease progression. Neuroprotection could be regarded as valuable therapeutic approach in SMA 71 . CT-1 defi ciency causes increased motoneuron cell death in spinal cord and brainstem nuclei of mice during a period between embryonic day 14 and the fi rst postnatal week.…”
Section: Cancermentioning
confidence: 99%
“…showed that cardiotrophin-1 delivery to SMA mutant mice resulted in protection of proximal and distal motoneurons, which was present even in postnatal period [106]. In this study, cardiotrophin-1 was delivered by intramuscular injection with an adenoviral vector expressing cardiotrophin-1 and it was able to improve survival and delay the motor defect in SMAΔ7 mice in neurons even at low doses.…”
Section: Neurotrophic Compoundsmentioning
confidence: 74%
“…Finally, substances with a neuroprotective action, (such as cardiotrophin-1), 50 and genetic conversion of the SMN 2 gene into SMN 1 , 51 are also the subject of therapeutic proposals being studied.…”
Section: Future Prospects For Diagnosis and Treatment Of Smamentioning
confidence: 99%